Arabiyya : recipes from the life of an Arab in diaspora - Assil, Reem; Katz, Emily (Communication strategist) (Ten Speed Press, 2022)
"Arabiyya celebrates the alluring aromas and flavors of Arab food and the welcoming spirit with which they are shared. Written from her point of view as an Arab in diaspora, Reem takes readers on a journey through her Palestinian and Syrian roots, showing how her heritage has inspired her recipes for flatbreads, dips, snacks, platters to share, and more. With a section specializing in breads of the Arab bakery, plus recipes for favorites such as Salatet Fattoush, Falafel Mahshi, Mujaddarra, and Hummus Bil Awarma, Arabiyya showcases the origins and evolution of Arab cuisine and opens up a whole new world of flavor"--Inside cover.